A Case Review: Reframing School-Based Practices Using a Critical Perspective. (2nd October 2015) - Phelan, Shanon K.; L. Ng, Stella
ABSTRACT: It is well established in the literature that school-based practice is fraught with challenges such as acquisition of appropriate and sufficient resources, communication barriers among professionals, parental burden, and redundancies and gaps in services. The purpose of this perspective paper is to reframe potentially problematic school-based practices using a critical social science perspective, suggesting a vision and strategies for therapists working in the context of school-based practice. We illustrate our approach with a case example. To reframe school-based practices, we begin with Jill's case, exploring it through a critical lens to identify potential issues and opportunities for change. We then trace these findings to our larger dataset from an ongoing program of research to ensure relevance to the broader context of school-based practice. Reframing of three school-based practice issues is discussed from: (a) advocacy by proxy to collaborative dialogue, (b) governing texts to guiding texts, and (c) playing the "right" part to having a voice. Although this is a perspective paper based on a case exemplar, we posit how we may reframe and rethink school-based practices in pediatric rehabilitation. We suggest that only with a genuine shift in our professional values will we see the enactment of collaborative practice in school-based settings.